Correlation between Leukocyte Count and Lymphatic Neutrophil Ratio to Procalcitonin in Covid-19 Confirmed Patients at Gresik Regional General Hospital: Hubungan Jumlah Leukosit dan Rasio Neutrofil Limfosit Terhadap Procalcitonin pada Pasien Terkonfirmasi Covid-19 di Rumah Sakit Umum Daerah Gresik - Verdiana, Verdiana; Puspitasari, Puspitasari (Universitas Muhammadiyah Sidoarjo, 2023)
Covid-19 is a new type of virus that attacks the respiratory system and can infect humans, which can cause respiratory illness and death from acute pneumonia. Hematology and procalcitonin are laboratory investigations that are often used. This study aims to determine the relationship between the results of the examination of the leukocyte count and the ratio of neutrophil lymphocytes to procalcitonin in patients with confirmed Covid-19. This type of research uses a cross sectional design using a purposive random sampling technique that uses secondary data. Research data collection was carried out in June 2022 at the Ibnu Sina Gresik Hospital Laboratory. Statistical test using Spearman correlation test. Based on the results of the study, it was found p = 0.481, indicating that the results were not statistically significant with the correlation coefficient (r) showing a negative value of 0.134, so it can be concluded that there is a very weak relationship between the number of leukocytes and procalcitonin in patients with confirmed Covid-19. A decrease in the number of leukocytes by 1 cell/µl can increase procalcitonin levels by 0.134 ng/ml and based on the results p = 0.491 indicating that the results are not statistically significant with a correlation coefficient value (r) of 0.131 so that it shows a very weak correlation between the ratio relationship neutrophil lymphocytes to procalcitonin in patients with confirmed Covid-19.